Brief research report pesticide occupational exposure leads to significant inflammatory changes in normal mammary breast tissue - da Silva, Ruan Gabriel Soares; Ferreira, Mariane Okamoto; Komori, Isabella Mitsu Suo; Oliveira, Henrique Rodrigues Menezes; Machado, Murilo Galvani; Orrutea, Julia Fernandes Gois; Alves, Fernanda Mara; dos Santos Jaques, Hellen; da Silva, Janaína Carla; de Souza, Janoário Athanazio; Rech, Daniel; Panis, Carolina (Frontiers in Public Health, 2023)
Studies have documented the high occurrence of several tumors, including female breast cancer, in populations occupationally exposed to pesticides worldwide. It is believed that in addition to direct DNA damage, other molecular alterations that indicate genomic instability are associated, such as epigenetic modifications and the production of inflammation mediators. The present study characterized the profile of inflammatory changes in the breast tissue of women without cancer occupationally exposed to pesticides. In samples of normal breast tissue collected during biopsy and evaluated as negative for cancer by a pathologist, oxidative stress levels were assessed as inflammatory markers through measurements of lipoperoxides and total antioxidant capacity of the sample (TRAP) by high-sensitivity chemiluminescence, as well as levels of nitric oxide (NOx) metabolites. The levels of inflammation-modulating transcription factors PPAR-γ (peroxisome proliferator-activated receptor gamma) and NF-κB (nuclear factor kappa B) were also quantified, in addition to the pro-inflammatory cytokines tumor necrosis factor-alpha (TNF-α) and interleukin 12 (IL-12). The levels of lipoperoxides, TRAP, and NOx were significantly lower in the exposed group. On the other hand, PPAR-γ levels were increased in the breast tissue of exposed women, with no variation in NF-κB. There was also a rise of TNF-α in exposed women samples without significant variations in IL-12 levels. These findings suggest an inflammatory signature of the breast tissue associated with pesticide exposure, which may trigger mechanisms related to mutations and breast carcinogenesis.